Double Higgs production at FCC-he and prospects for measurements of self-coupling. (May 2015) - Kumar, Mukesh; Ruan, Xifeng; Cornell, Alan S; Islam, Rashidul; Mellado, Bruce
Abstract: The measurement of the triple Higgs boson coupling is one of the most important goals of the Higgs physics program in present and future collider experiments. This would provide the first direct information on the Higgs potential, which is responsible for electroweak symmetry breaking mechanism. We present a double Higgs production scenario at the Large Hadron-Electron Collider (LHeC) and Future Circular Hadron-Electron Collider (FCC- he) through e - p collisions, which will provide information about trilinear coupling and the possibility of probing new physics, if there is any. The LHeC will provide e - beams to collide head-on with proton beams of 7 TeV from the Large Hadron Collider (LHC). The prospect of replacing the LHC with the high energy FCC, with proton beams of 50 TeV, is used for FCC-he studies. Energy of the e - is taken to be 60 GeV for both LHeC and FCC-he. Effects of non-standard CP-even and CP-odd couplings for hhh, hWW and hhWW have been studied and constrained at a 95% C.L.